Use of donor milk in the neonatal intensive care unit. Issue 1 (February 2017) - de Halleux, Virginie; Pieltain, Catherine; Senterre, Thibault; Rigo, Jacques
Summary: Own mother's milk is the first choice in feeding preterm infants and provides multiple short- and long-term benefits. When it is unavailable, donor human milk is recommended as the first alternative. Donor milk undergoes processing (i.e. pasteurization) to reduce bacteriological and viral contaminants but influences its bioactive properties with potentially fewer benefits than raw milk. However, there is no clinical evidence of health benefit of raw compared to pasteurized human milk, and donor milk maintains documented advantages compared to formula. Nutrient content of donor and own mother's milk fails to meet the requirements of preterm infants. Adequate fortification is necessary to provide optimal growth. There are significant challenges in providing donor milk for premature infants; therefore, specific clinical guidelines for human milk banks and donor milk use in the neonatal intensive care unit should be applied and research should focus on innovative solutions to process human milk while preserving its immunological and nutritional components. In addition, milk banks are not the only instrument to collect, process and store donor milk but represent an excellent tool for breastfeeding promotion.